Pengaruh Sikap Religiusitas terhadap Perilaku Hidup Bersih dan Sehat (PHBS) Masyarakat Kelurahan Dusun Curup Kabupaten Rejang Lebong - Yanuarti, Eka (STAIN Curup, 2018)
This study aims to determine the influence of religious attitudes toward PHBS community at RejangLebong district. This research is field research, with approach of mixed methods, concurrent triangulation model. The results showed that the attitude of religiosity has a contribution of 83.80% to the community PHBS Dusun Curup. The attitude of the religiosity of society has an influence on the clean behavior of them, as the religious ritual dimension brings influence to the behavior of using clean water in everyday life. Then the dimension of religious consequences in the community in bringing influence on community behavior in combating mosquito larvae. The influence of the attitude of religiosity on the Psychic / Mental health of society is to make people obedient to the leadership who gave command that is Allah SWT. Coachingpeople have a high legislature in carrying out the duty that is given to them. Making people have an optimistic attitude in facing the future. Reassuring people's souls. Encouraging the community face the problems of life with a patient and steadfast heart.Educating people to be sportive and gentleman to admit their mistakes and sin. Avoiding people from doing despicable and evil. While the influence of medical health, has not brought significant influence as there are still many people who smoke, smoking habit has been evenly done by the fathers, not only fathers, but also the youth who are still in school and have not had a job.